2017
DOI: 10.1002/mame.201700069
|View full text |Cite
|
Sign up to set email alerts
|

Facile Incorporation of Silver Nanoparticles into Quaternized Poly(2-(Dimethylamino)Ethyl Methacrylate) Brushes as Bifunctional Antibacterial Coatings

Abstract: A simple strategy to fabricate bifunctional antibacterial coatings via in situ synthesis and incorporation of silver nanoparticles (AgNPs) into quaternized poly(2‐(dimethylamino)ethyl methacrylate) (qPDMAEMA) brushes without using any reducing agents is reported. PDMAEMA brushes are prepared on Si wafer substrates via surface‐initiated reverse atom transfer radical polymerization, which then are quaternized with ethyl bromide and hexyl bromide, respectively. The resulting qPDMAEMA‐AgNP nanocomposite coatings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 63 publications
1
21
0
1
Order By: Relevance
“…These coatings also allow for the modification of surface charge nanoparticle, that can be adjusted to facilitate MNPs elimination from the body [69]. Biopolymers most frequently used with this purpose are PEG [70], poly-d-l-(lactic-co-glycolic acid) (PLGA) [71], polyactic acid (PLA), poly(caprolactone) (PCL) [72], poly(dimethyl aminoethyl methacrylate) (PDMAEMA) [73], Poly(N-isopropylacrylamide) (PNIPAM) [74], Dextran [75], Chitosan [76], poly(urethanes) (PUs) [77] and poly(ethyelene imine) (PEI) [78]. All of these polymers can undergo degradation processes to be broken down into products that can be safely processed in the body.…”
Section: Toxicity Vs Efficacy Of Mnps In Biomedical Applicationsmentioning
confidence: 99%
“…These coatings also allow for the modification of surface charge nanoparticle, that can be adjusted to facilitate MNPs elimination from the body [69]. Biopolymers most frequently used with this purpose are PEG [70], poly-d-l-(lactic-co-glycolic acid) (PLGA) [71], polyactic acid (PLA), poly(caprolactone) (PCL) [72], poly(dimethyl aminoethyl methacrylate) (PDMAEMA) [73], Poly(N-isopropylacrylamide) (PNIPAM) [74], Dextran [75], Chitosan [76], poly(urethanes) (PUs) [77] and poly(ethyelene imine) (PEI) [78]. All of these polymers can undergo degradation processes to be broken down into products that can be safely processed in the body.…”
Section: Toxicity Vs Efficacy Of Mnps In Biomedical Applicationsmentioning
confidence: 99%
“…Nonactive solid‐supported polymer brushes play a role in antimicrobial applications, when combined with active elements such as antibiotic, antimicrobial peptides and nanoparticles. For instance, poly(sulfobetaine methacrylate) and poly(carboxybetaine methacrylate) brushes were used to embed silver nanoparticles which allocate the antibacterial activity . The combination of antimicrobial NP and zwitterions shows outstanding antimicrobial activity of the membrane, where the bacterial population was reduced by 100% after 6 h incubation time.…”
Section: Application Of Functional Surfacesmentioning
confidence: 99%
“…In recent years, the use of biodegradable polymers has gained widespread attention for usage as food packaging due to its renewable, biodegradable, and nontoxic nature . The most advantages of biodegradable polymers are low cost, bio compatibility, and having film‐forming properties . In spite of many advantages, the high capacity of moisture absorbance of these polymers leads to grow microbes such as molds, yeast, and bacteria, which can cause food decay.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that antimicrobial compounds can inhibit the growth of foodborne pathogens . The potential application of these films with antimicrobial activities would allow surface contact with food that could help control the growth of food pathogens . Silver (Ag) nanoparticles are excellent candidates for research because of their high antibacterial potential .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation